Simulation of processes in optochemotronic emitter with electrodes modified by Langmuir-Blodgett technique - Vasyanovitch, D.A.; Zholudov, Yu.T.; Rozhitskii, N.N. (Functional Materials, 2004)
The light generation possibility in an optochemotronic device of liquid phase optoelec -tronics with the working electrode modified by means of Langmuir-Blodgett technique for thin-film deposition has been studied using mathematical simulation. The kinetics of the emitting centers and photons flux density have been calculated for so configured opto -chemotronic emitter with 9,10-diphenylanthracene as the working electrochemiluminophor being in the film and in the bulk of solution. The possibility to obtain the inversion of electronic level population in the organic luminophor molecules and laser generation under non-optical electrochemical excitation in the optochemotronic emitter has been shown. Методом математического моделирования изучена возможность генерации света в оптохемотронном устройстве жидкофазной оптоэлектроники с рабочим электродом, модифицированным по технологии Ленгмюра-Блоджетт нанесения тонких пленок. Рассчитана кинетика излучательных центров и плотность потока фотонов для подобной конфигурации когерентного оптохемотронного излучателя с 9,10-дифенилантраценом в качестве рабочего электрохемилюминофора, находящегося в пленке и в растворе. Показана возможность получения инверсной населенности электронных уровней молекул органических люминофоров и лазерной генерации при неоптическом электрохимиче-я:ом возбуждении в оптохемотронном излучателе. За методом математичного моделювання вивчено можливість генерації світла в оптохемотронному пристрої рідиннофазної оптоелектроніки з робочим електродом, модифікованим за технологією Ленгмюра-Блоджетт нанесення тонких плівок. Розраховано кінетику випромінювальних центрів та густини потоку фотонів для подібної конфігурації когерентного оптохемотронного випромінювача з 9,10-дифенілантраценом у якості робочого електрохемілюмінофора, що знаходиться у плівці та в розчині. Показано можливість отримання інверсної населеності електронних рівнів молекул органічних люмінофорів та лазерної генерації при неоптичному електрохімічному збужденні в оптохемотронному випромінювачі.